EIGHTH INTERNATIONAL WORKSHOP ON AGGLUTINATED FORAMINIFERA; CLUJ-NAPOCA, SEPTEMBER 7–13, 2008. - FILIPESCU, Sorin; KAMINSKI, M.A. (2008)
The International Workshop on Agglutinated Foraminifera (IWAF) is a series of meetings held approximately every four years devoted primarily to the systematics, (palaeo)ecology and evolution of the largest single group of foraminifera.